Application of a simple scoring scale to predict prognosis of poor-grade subarachnoid haemorrhage using intraventricular haemorrhage - Shuto Fushimi; Taisuke Akimoto; Makoto Ohtake; Yu Iida; Shigeta Miyake; Ryosuke Suzuki; Satoshi Hori; Jun Suenaga; Yasunobu Nakai; Katsumi Sakata; Tetsuya Yamamoto (Scientific Reports)
Abstract Intraventricular haemorrhage (IVH) is a key prognostic factor for subarachnoid haemorrhage (SAH). However, no simple or rapid scoring method for its evaluation exists. We aimed to modify and validate a simple scale for rapid IVH grading. We engaged two study groups to generate scores and examine their utility. Study 1 identified prognostic factors in poor-grade SAH and developed a prognostic scoring system. Study 2 evaluated the utility of the score by analysing data from a multicentre patient registry, including all severity levels, and confirmed its generalisability. Outcomes were defined using the modified Rankin scale (score ≥ 3: poor outcome). Study 1 (including 110 patients with poor-grade SAH) created a simple IVH score (IVHAge) based on two slices of computed tomography images and confirmed that it was as predictive as the modified Graeb score (area under the curve: IVHAge score, 0.815; modified Graeb score, 0.752). Study 2 examined 493 patients and found that for each 1-unit increase in the IVHAge score, the odds of a poor outcome increased by 37% (unit odds ratio, 1.37; 95% confidence interval 1.10–1.70; P = 0.005). The IVHAge score, which comprises a simplified IVH score and age-related factors, has prognostic value and is suitable for rapid clinical application.